Selenium Supplementation in Pregnancy-Maternal and Newborn Outcomes - Koushik Biswas; James McLay; Fiona M. Campbell (Journal of Nutrition and Metabolism)
Background. Several studies have suggested that increased oxidative stress during pregnancy may be associated with adverse maternal and foetal outcomes. As selenium is an essential mineral with an antioxidant role, our aim was to perform a systematic review of the existing literature reporting the effects of selenium supplementation during pregnancy on maternal and neonatal outcomes. Materials and Methods. Six electronic databases (Medline, Embase, Cochrane Library, Web of Science, Scopus, and PubMed) were searched for studies reporting the effects of selenium supplementation during pregnancy and the postpartum period on maternal and neonatal outcomes. Only randomised controlled trials on human subjects reported in English and published up to October 2021 were included. Quality assessments were conducted using the modified Downs and Black quality assessment tool. Data were extracted using a narrative synthesis. Results. Twenty-two articles were included in our systematic review (seventeen reported on maternal outcomes, two on newborn outcomes, and three on both). Maternal studies reported the effects of selenium supplementation in the prevention of thyroid dysfunction, gestational diabetes, pregnancy-induced hypertension/preeclampsia, oxidative stress, postpartum depression, premature rupture of membranes, intrauterine growth retardation, breastmilk composition, and HIV-positive women. Newborn studies reported the effects of maternal selenium supplementation on foetal oxidation stress, foetal lipid profile, neonatal hyperbilirubinemia, and newborn outcomes in HIV-positive mothers. The majority of studies were inappropriately designed to establish clinical or scientific utility. Of interest, four studies reported that selenium supplementation reduced the incidence of thyroid dysfunction and permanent hypothyroidism during the postpartum period by reducing thyroid peroxidase and thyroglobulin antibody titres. Conclusion. The evidence supporting selenium supplementation during pregnancy is poor and there is a need for appropriately designed randomised controlled trials before routine use can be recommended.